2021
DOI: 10.3390/genes12040466
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Chimeric RNAs in Non-Cancerous Cells

Abstract: Gene fusions and their products (RNA and protein) have been traditionally recognized as unique features of cancer cells and are used as ideal biomarkers and drug targets for multiple cancer types. However, recent studies have demonstrated that chimeric RNAs generated by intergenic alternative splicing can also be found in normal cells and tissues. In this study, we aim to identify chimeric RNAs in different non-neoplastic cell lines and investigate the landscape and expression of these novel candidate chimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Further, improving these computational tools, validating the functional effects of individual chimeric RNAs in cancer cell lines, and conducting clinical trials could revolutionize the precision oncologybased treatment approaches. Recent studies identified a vast amount of chimeric RNAs in healthy human tissues and normal cells (Babiceanu et al, 2016;Chen et al, 2021;Singh et al, 2020). Chimeric RNAs could be generated by cis-SAGe and trans-splicing in normal human cells .…”
Section: How Patient-specific Chimeric Rnas Could Be Useful Targets I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, improving these computational tools, validating the functional effects of individual chimeric RNAs in cancer cell lines, and conducting clinical trials could revolutionize the precision oncologybased treatment approaches. Recent studies identified a vast amount of chimeric RNAs in healthy human tissues and normal cells (Babiceanu et al, 2016;Chen et al, 2021;Singh et al, 2020). Chimeric RNAs could be generated by cis-SAGe and trans-splicing in normal human cells .…”
Section: How Patient-specific Chimeric Rnas Could Be Useful Targets I...mentioning
confidence: 99%
“…However, only a small fraction of chimeric RNAs were validated as functional (Shi et al, 2021; Sun & Li, 2022). Further, the analysis of human transcriptome data from different normal tissues reveals that chimeric RNAs are also prevalent in healthy tissues (Babiceanu et al, 2016; Chen et al, 2021; Singh et al, 2020). However, their functional role in normal tissues is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Chimeric RNAs have been found to be generated from trans- splicing and cis -splicing between adjacent genes ( cis -SAGe), without genomic aberrations. 22 Recent studies have suggested that chimeric RNAs generated by cis -SAGe play a potentially important role in normal biological functions in humans. 23 There have been few studies of cis -SAGe chimeric RNAs because only a small number of cis -spliced RNA chimeras have been experimentally confirmed in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been further supplemented by read-through chimeras such as SLC45A3-ELK4 (7) and chimeras such as ASTN2-PAPPAAS (8), which are produced without noted changes to subject DNA and have demonstrated functions relevant to cancer pathogenesis. There has been a significant effort to catalogue chimeric RNAs in various diseases and cell types to identify such novelties (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%